Surgical treatment hyperparathyroidism. Round Table - Morelli, Raúl; Fernández, Juan; Balboa, Oscar; Ventura, Juan; Vercelli Retta, Jorge (Cirugía del Uruguay, 1994)
Primary hyperparathyroidism is a fascinating disease with a multifaceted clinical picture. Some patients may have only signs and minor symptoms but in others the disease may put the life of the sick person at stake. Due to the extreme variability of its clinical picture the diagnosis of primary hyperparathyroidism very often depends on the sagacity of the doctor, surgeon and anatomical pathologist working on set.